Selection of Raw Material Suppliers for Injection Shoe Making Using the Fuzzy Analytical Hierarchy Process (FAHP) Method at PT. XYZ - Amanda, Gadis Elvira; Ernawati, Dira (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
Companies in the fashion sector are required to continue to maintain the quality of their products to survive in the local and international markets. This makes a company in Sidoarjo that produces injection shoes contribute to maintaining product quality by maintaining the quality of raw materials. Suppliers play an important role in ensuring the quality of raw materials. The company must be able to choose the right supplier in order to ensure the availability, quality, and quantity of raw materials that meet the company’s criteria. This research aims to determine the best flyknit raw material suppliers based on predetermined criteria using the fuzzy analytical hierarchy process method. In this study, there are 5 main criteria in choosing a flyknit supplier, namely price, quality, delivery, service, and communication system. The results showed that the order of the best flyknit raw material suppliers at PT XYZ with the greatest value was supplier 4 with a value of 0.179. Then in second place is supplier 2 with a value of 0.178, in third place is supplier 6 with a value of 0.177, in fourth place is supplier 3 with a value of 0.175, fifth place is supplier 1 with a value of 0.161. and the last order is supplier 5 with a value of 0.129. In conclusion, the FAHP method can be effectively used in selecting suppliers of flyknit raw materials at PT. XYZ because this method provides more objective and structured results.